2016
DOI: 10.1016/j.tecto.2015.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Extrusion vs. duplexing models of Himalayan mountain building 2: The South Tibet detachment at the Dadeldhura klippe

Abstract: Himalayan mountain building has been dominantly explained by two types of models: extrusion and duplexing. To elucidate possible roles of these mechanisms during emplacement of the Himalayan crystalline core, we investigate an area speculated to contain the southern leading edge of the crystalline core: the northeastern margin of the Dadeldhura klippe, western Nepal. We found a ~700 m thick, primarily top-to-the-north shear zone within the klippe; we term this the Tila shear zone. The shear zone occurs within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 181 publications
(355 reference statements)
0
14
0
Order By: Relevance
“…Sample JD‐06D is from the middle of the GHS on the northeast flank of the Karnali klippe. It is located within the Tila shear zone (Figure ; He et al, ). The CPO fabric forms a weakly asymmetric type I crossed girdle suggesting a top‐to‐the‐SSE sense of shear, inconsistent with the top‐to‐the‐north sense of shear interpretation of He et al (), but consistent with top‐to‐the‐SE shear bands observed in a nearby sample (JD‐06B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Sample JD‐06D is from the middle of the GHS on the northeast flank of the Karnali klippe. It is located within the Tila shear zone (Figure ; He et al, ). The CPO fabric forms a weakly asymmetric type I crossed girdle suggesting a top‐to‐the‐SSE sense of shear, inconsistent with the top‐to‐the‐north sense of shear interpretation of He et al (), but consistent with top‐to‐the‐SE shear bands observed in a nearby sample (JD‐06B).…”
Section: Resultsmentioning
confidence: 99%
“…Top‐to‐the‐SW shear‐sense indicators are abundant in the MCT high‐strain zone and sparse above it. A top‐to‐the‐north structure, the Tila shear zone, has been described in the middle of the GHS on the north flank of the Karnali klippe (Figure a; He et al, ). However, we have observed ambiguous evidence for top‐to‐the‐north shear at that location (see also Soucy La Roche et al, ).…”
Section: Geology and Structure Of The Karnali Klippementioning
confidence: 99%
See 2 more Smart Citations
“…8), spatial convergence ( Figs. 1 and 10), and consistent top-to-the-north kinematics suggest that linkage was possible, if not probable (Yin et al, 1994(Yin et al, , 1999(Yin et al, , 2010Yin, 2006;Webb et al, 2007Webb et al, , 2017He et al, 2016). The South Tibetan detachment system forms the roof fault of the North Himalayan domes (e.g., Larson et al, 2010), exposed just to the south of the Yarlung suture zone (Fig.…”
Section: Lithospheric-scale Tectonics and The Gangdese Culmination Modelmentioning
confidence: 77%